2020
DOI: 10.3389/fmicb.2019.03131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Characterization of the First Hypovirus Identified in Fusarium oxysporum

Abstract: A novel mycovirus named Fusarium oxysporum f. sp. dianthi hypovirus 2 (FodHV2) has been identified infecting isolates Fod 408 and Fod 409 of Fusarium oxysporum f. sp. dianthi from Morocco. The genome of FodHV2 is 9,444 nucleotides long excluding the poly(A) tail, and has a single open reading frame encoding a polyprotein. The polyprotein contains three highly conserved domains of UDP glucose/sterol glucosyltransferase, RNA-dependent RNA polymerase, and viral RNA helicase. In addition, particular residues of Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Numerous mycoviruses have been described from different families, infecting many phytopathogenic fungi and entomopathogenic fungi [ 2 , 8 , 46 ]. However, among the hundreds of mycoviruses described so far, only six mycoviruses have been identified in F. oxysporum , an important phytopathogenic species [ 34 , 35 , 36 , 37 , 38 , 39 ], with no reports of any viruses belonging to the proposed family “Alternaviridae”. FoAV1 is the first alternavirus described to infect F. oxysporum .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous mycoviruses have been described from different families, infecting many phytopathogenic fungi and entomopathogenic fungi [ 2 , 8 , 46 ]. However, among the hundreds of mycoviruses described so far, only six mycoviruses have been identified in F. oxysporum , an important phytopathogenic species [ 34 , 35 , 36 , 37 , 38 , 39 ], with no reports of any viruses belonging to the proposed family “Alternaviridae”. FoAV1 is the first alternavirus described to infect F. oxysporum .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large number of hypovirulent mycoviruses, such as CHV1 [ 13 ] and SsHADV1 [ 49 ], have been identified and explored as potential biocontrol agents against fungal diseases [ 4 , 32 , 33 ]. However, until now, only two mycoviruses, FodV1 and FoOuLV1, isolated from F. oxysporum , exerted hypovirulent effects [ 34 , 35 , 36 , 37 , 38 , 39 ]. FoAV1 exhibited a good biological control effect for Fusarium wilt, suggesting that it may be a good resource for controlling Fusarium wilt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the Sclerotinia sclerotiorum strain Ep-IPN and observed that its attenuating factor (dsRNA) could be transferred to a strain with normal vegetative affinity (Ep-IPNA183) through soil and rape leaves, which caused the virulence of the normal strain to decline and protected the plants from any damage caused by the latter strain (Azhar et al, 2019;Torres-Trenas et al, 2020). However, there are many problems that need to be solved when fungal viruses are applied in actual plant production.…”
Section: Fungal Virusesmentioning
confidence: 99%
“…For instance, Cryphonectria parasitica hypovirus 1 (CHV1) has been used to control chestnut blight caused by Cryphonectria parasitica [9,10]. In Fusarium species, more than 30 mycoviruses have been identi ed and fully sequenced [9][10][11][12][13][14]. 4 mycoviruses were associated with hypovirulence of the host Fusarium, and notably, 3 viruses were from F. graminearum [15][16][17].…”
Section: Introductionmentioning
confidence: 99%